Proto Language Relationship with Mandailing Language - Rahmawati Rahmawati (Randwick International of Education and Linguistics Science Journal, 2022)
This study aims to examine the kinship of the Proto language with the Mandailing language. This research uses qualitative and quantitative methods. Qualitative method by grouping languages according to their level of kinship. The quantitative method is carried out using lexicostatistics techniques. Data collection techniques used in the form of recording techniques and recording techniques. The data used in this research is basic vocabulary which contains a list of 200 Swadesh vocabularies. (1) Identical pairs of Proto and Mandailing have 35 vocabularies. (2) Pairs Have Phonemic Correspondence in Proto and Mandailing, there are 2 vocabularies. (3) Phonetic similarities between Proto and Mandailing have 2 vocabularies. (4) One different phoneme in Proto and Mandailing languages has 16 vocabularies. The overall similarity of vocabularies from Proto and Mandailing which can be concluded is that there are 55 vocabularies or about 28%. That is, the percentage of kinship between the two is 28%. This percentage indicates that the Proto and Mandailing languages belong to the same family.